Auxiliary Power Filters Design for Electric-drive Rail-grinding Car - YANG Feng; XIAO Ke (机车电传动)
Harmonic-generating mechanism of rectifier and inverter for electric-drive rail-grinding car was briefly analyzed, and necessity of setting DC and AC filters for the converters was elaborated. Parameters design of DC filter and the AC filter was focused on and checked by simulation, good harmonic-suppressing effect of which has been shown in simulation as well as in actual experiment.